Assessing the economic value of academic libraries - Melo, Luíza Baptista; Sanches, Tatiana; Matos, Gaspar; Torres, Patrícia (Qualitative and Quantitative Methods in Libraries; Vol 7 No 3 (2018): September 2018 Issue, 2019)
The assessment of academic libraries is an important management issue of the services and of Library Advocacy. Determining the monetary value of the services may be an interesting element at a time when there are constraints on the budgets of the institutions. The main aim of this paper is to calculate the tangible value in monetary terms of certain services of two libraries of the University of Lisbon. In this task we use six statistical indicators: document loans, accesses to Internet; accesses to computers, accesses to journals, training and interlibrary loans. The method to calculate the monetary value for a specialized quality service is to verify the current market value of the service, ie., the current price of the service that can be bought or sold in the free market (ISO16439:2014). According to this investigation we calculate the monetary values for these indicators. The cost-benefit value is also calculated, that is, the return on investment, the relationship between the total economic benefit of these indicators and the total resources invested in the library according to these indicators.